COVID-19 mRNA vaccine may trigger subacute thyroiditis - Mehmet Sözen; Ömercan Topaloğlu; Berrin Çetinarslan; Alev Selek; Zeynep Cantürk; Emre Gezer; Damla Köksalan; Taner Bayraktaroğlu (Taylor & Francis Group, 2021)
Subacute thyroiditis is the most common cause of painful thyroiditis, which usually occurs after an acute viral upper respiratory tract infection. Rare cases of subacute thyroiditis have been reported after administration of viral vaccines. Here, we report four cases of subacute thyroiditis after administration of the COVID-19 mRNA vaccine (Pfizer/BioNTech®). We describe the clinical, laboratory and imaging features of five cases of subacute thyroiditis after COVID-19 mRNA vaccine (Pfizer/BioNTech®). COVID-19 mRNA vaccine (Pfizer/BioNTech®)-associated subacute thyroiditis may present with clinical findings typical of classic subacute thyroiditis such as fever, neck pain, weakness, and tremor within a few days following vaccination. Subacute thyroiditis may be focal or may progress with diffuse bilateral involvement. Depending on the extent of subacute thyroiditis involvement, significant increases in acute-phase reactants can be observed. COVID-19 mRNA vaccine (Pfizer/BioNTech®) associated subacute thyroiditis responds quite well to non-steroidal anti-inflammatory therapy. Clinicians should be aware of the risk of developing subacute thyroiditis after vaccination.